2009
DOI: 10.1017/s0014479708007096
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF VAPOUR PRESSURE DEFICIT ON LEAF WATER RELATIONS OF COCOS NUCIFERA IN NORTHEAST BRAZIL

Abstract: SUMMARYDaily courses of leaf gas exchange and leaf water potential (Ψleaf) of green dwarf coconut palm (Cocos nucifera) were measured in irrigated plantations on the wet coastal plateau and in a dry semi-arid area of northeast Brazil. At both sites, significant correlations were obtained between stomatal conductance (gs) and vapour pressure deficit (VPDair), Ψleaf and VPDair, leaf transpiration (E) and gs, and E-Ψleaf. Despite these similar relationships between sites, stronger correlations involving gs-VPDair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Afterwards, the decrease in P N until late afternoon may be related to the higher afternoon T a and VPD. Similar pattern was shown by palms such as coconut (Passos et al 2009), as well as by other tree species such as citrus (Machado et al 2002). Temperature can influence enzymatic reactions, and the physiological and biochemical responses of cell membranes, and thus became the main factor to impact photosynthetic dynamics of the plant (Li et al 2011;Chen et al 2012;Oukarroum et al 2012;Suleman et al 2013).…”
supporting
confidence: 67%
“…Afterwards, the decrease in P N until late afternoon may be related to the higher afternoon T a and VPD. Similar pattern was shown by palms such as coconut (Passos et al 2009), as well as by other tree species such as citrus (Machado et al 2002). Temperature can influence enzymatic reactions, and the physiological and biochemical responses of cell membranes, and thus became the main factor to impact photosynthetic dynamics of the plant (Li et al 2011;Chen et al 2012;Oukarroum et al 2012;Suleman et al 2013).…”
supporting
confidence: 67%
“…It is known that climate elements mainly PPFD, temperature and air RH influence directly gas exchange of all plant species and its impact is of high importance to physiology of production, once productivity depends highly on the P N throughout the crop cycle (Taiz & Zeiger, 2009). Like all palms (Tucci et al, 2010;Prado et al 2001;Passos et al, 2009), gariroba palm presented diurnal variation of gas exchange with a performance consistent with that of photosynthetic metabolism of C3 plants (Larcher, 2000), both in May and in August (Figure 2 and 3).…”
Section: Resultsmentioning
confidence: 70%
“…On the other hand, Larcher (2000), suggested for C3 trees, maximum P N between 10 and 15 µmol m . Differently to what has been observed for palms of more economical importance like coconut (Gomes & Prado, 2007;Gomes et al, 2008;Passos et al, 2009), oil palm (Dufrêne & Saugier, 1993;Suresh et al, 2012) and lately the heart-of-palm producer palms (Tucci et al, 2007(Tucci et al, , 2010Lavinsky et al, 2014;Pereira et al, 2014), no references to gariroba palms gas exchange were found.…”
Section: Received On February 16 2017; Accepted On February 9 2018mentioning
confidence: 76%
See 1 more Smart Citation
“…The efforts to correlate it with environmental parameters are not always successful. Stomatal conductance of sunlit leaves depends on air temperature and air CO 2 concentration, but the air vapor pressure deficit and the soil water status also play an important role (JARVIS, 1976;PASSOS et al, 2009). The following two parts of the soil-water-atmosphere system need special attention in mechanistic modeling of plant water stress:…”
Section: Developmentmentioning
confidence: 99%